Pluralism comes of age : American religious culture in the twentieth century - Lippy, Charles H. (M.E. Sharpe, 2000)
"Beginning with the Victorian age and the end of the nineteenth century, Lippy's narrative moves through the shifting power of Protestantism and American Catholicism and into the period of immigration and pluralism that has characterized our country's religious experience. His later chapters include coverage of the Jewish experience, African-American religion, Native American traditions, the ecstatic personal expressions of conversion that mark the evangelical movements, the politics of religion, the proliferation of sects and cults, and the many strands of religious thought in this century."--Jacket